Justicia chamánica Mapuche y discriminación en los tribunales chilenos: las luchas de la jueza LGBT Karen Atala por la custodia de sus hijas y por el pluralismo jurídico. - BACIGALUPO, ANA MARIELLA; LE BONNIEC, FABIEN (Nomadías)
Judge Karen Atala framed her child custody case against the Chilean Supreme Court within Indigenous Mapuche "shamanic justice," the "spirit of the law," and human rights. We analyze what Atala's case contributes to the literature on sexual diversity, sorcery, and the spirit of the law in both Chilean and Mapuche histories of justice. The case engages the spirit of the law in two senses. First, it reveals the lack of separation between religious and secular law, demonstrating that religion is profoundly embedded in the law, both for the state and for the Mapuche. Second, it refers to the intention behind the law and its interpretation and enforcement, which haunts even the most literalist, secular visions of law. After her spiritual transformation, Atala practiced the spirit of Mapuche customary law in the courts but formally justified her judgments using the letter of the Chilean law, demonstrating a fluidity between law and spirituality.